The enactment of assessment for learning to account for learners' mathematical understanding - Sedibeng, Khutso Makhalangaka (My University, 2022)
The purpose of this study was to document my enactment of the five key strategies of assessment for learning in my mathematics classroom to account for learners' mathematical understanding. I used a constructivism teaching experiment methodology to explore learners' mathematical activities as they interacted in the classroom. Twenty-five learners from my Grade 10 mathematics class took part in the study. Data were gathered through classroom observations, written work samples from learners, and the teacher's reflective journal. My enactment of the five key strategies enabled learners to participate in classroom discussions, collaborate with their peers, and use self-assessment tools while engaging in classroom interactions. The major findings revealed that, through my enactment of the five key strategies, learners developed conceptual understanding, procedural fluency and strategic competence of the concepts taught. In addition, practices such as the development of lesson plans detailing how the five key strategies will be enacted in the classroom, use of comment – only feedback for grading learners’ work, creating a conducive learning environment to allow the use of peer and self-assessment allowed for a meaningful enactment of assessment for learning in my classroom. Strategies four and five, whose primary goal is to encourage learners' participation in the lesson, were critical in promoting learners' mathematical understanding.
Thesis (M. Ed. (Mathematics)) -- University of Limpopo, 2022
Keywords: Enactment; Assessment for learning; Account; Learners’ mathematical understanding; Collegiate learning assessment; Mathematical ability -- Testing; Behavior modification